Readability formulas: An analysis into reading index of prose forms - Revathi Gopal; Mahendran Maniam; Noor Alhusna Madzlan; Siti Shuhaida binti Shukor; Kanmani Neelamegam (Universitas Syiah Kuala, 2021)
Text comprehension will suffer if the readability level is not accessible to the students. Readability formulas predict text complexity, assisting in appropriate text selection that complements students' reading abilities to improve their language development. Therefore, the study aims to find out the reading index of the prose forms in the literature component catered to lower secondary school students ages 13 and 14 years old in Form One (seventh grade) and Form Two (eighth grade) classrooms in Malaysia. The reading index is measured by using four readability formulas which are Dale-Chall, Fog, SMOG, and Flesch-Kincaid that focuses on the words, sentences, syllables, and polysyllable words. These formulas are used to predict the level of difficulty of the prose forms. The reading index calculated from these readability formulas reveals the grade level of the prose forms. The grade level indicates the best age for reading and understanding the prose forms. Two prose forms were chosen as samples in the study. A passage is chosen from each prose form to be uploaded using the online tool. The indices obtained from the readability formulas predicted that both of the prose forms were below students' reading age. The study implicates reading index must be taken into consideration in literary texts selection because it is an indicator of the years of education that an individual requires to comprehend the literary text clearly. Suitable reading material at students' age level can enhance literature learning and teaching in the ESL classroom.